GIS application in oil and gas exploration & production activities based on past experience - Abd. Latef, Mohd. Zukhairi; Mahmud, Mohd. Razali (2006)
Exploration and Production (E&P) is the earliest activities done in oil and gas business. E&P lifecycle consists of Exploration, Appraisal, Development, Production and Abandonment phase. A lot of data types have been produced through this lifecycle. E&P activities are mainly divided into two areas namely subsurface and surface. For offshore activities, subsurface is an area below the seabed. These data consists of geological and geophysical (G&G) elements to analyze the hydrocarbon accumulations or prospects area. Surface consists of the data covered from the water column to the seabed data such as platform, pipeline and infrastructure data which support the E&P activities. Subsurface data produced are inclusive of seismic, well, drilling and reservoir engineering data. Seismic data consists of seismic sections, seismic navigation, seismic shot-points maps, bathymetry data, velocity, etc. A wildcat well will be drilled to gather information of the hydrocarbon properties and rock lithologies. Well data consists of well location, well logs, core samples, check shots, well testing and Vertical Seismic Profiling (VSP), reservoir pressure and sampling data, etc. Well data often aided by seismic data is used for appraisal rather than exploration. Surface data consists of facilities such as site survey data, platforms, pipelines, engineering drawings, Health, Safety and Environment (HSE) and others associated data. This paper is prepared to introduce and share knowledge of the data types produced from the E&P that contains geospatial elements and will be the basis for GIS applications in oil and gas business. Some findings from the past experience were reviewed to show the GIS applications in oil and gas exploration workflow.